WHAT IS THE RESEARCH IMPACT OF (THE IDEAL OF) SCIENTIFIC TRUTH? - Brauer, Rene; Dymitrow, Mirek; Worsdell, Filipe; Walsh, John (Journal of Education Culture and Society, 2021)
Aim. This paper elucidates how the emergent impact agenda is slowly but surely changing the normative framework of modern Western science. Method. The paper investigates conceptually the implications of the impact agenda for the research process. We outline a chronology around the evaluation regime of research impact and identify the causal mechanisms that change the disciplinary structure of the research ecosystem. We draw upon a sociological model of scientific knowledge production to contrast and discuss how impact facts mimic the process of scientific knowledge production but are geared towards a different end. Results. Our findings indicate that an explicit emphasis on societal contribution not only propositions a different purpose of research, but also changes the logic of research along its entire construction. The impact logic mimics the creation of scientific facts; nevertheless, as it is geared towards a different end, it hermetically seals itself from criticism as any form of scrutiny would otherwise undermine its own legitimacy. Conclusion. We conclude that only explicit acknowledgement of the adverse potential of the impact agenda can maintain science’s benefit to society. We argue that an emphasis on the advancement of knowledge, as opposed to impact, can maintain innovation and preempt social tension. The contribution of this paper lies in identifying the societal influence of the scientific ideal of truth, and articulating the unintended consequences of the impact agenda as the emerging impact or starve paradigm.